Pengaruh Transparansi, Akuntabilitas, Responsibilitas, Independensi, Dan Kewajaran Terhadap Kinerja Koperasi - Ni Kadek Dian Nanda Putri; Ni Wayan Alit Erlinawati (Hita Akuntansi dan Keuangan, 2023)
Performance is very important to measure in order to achieve a company goal. In cooperatives, performance is measured in two aspects, namely financial performance and management performance. In the current study, it will discuss and explore the relationship formed between Transparency, Accountability, Responsibility, Independence and Fairness in relation to the performance of cooperatives in Tegalalang District. The sample in this study amounted to 198 employees, all of whom were cooperative employees in the Tegalalang District. This study uses multiple linear regression analysis techniques with results showing that cooperative performance will increase when transparency, accountability, and responsibility increase. Fairness has no relationship to the level of performance of cooperatives in Tegalalang District.